Understanding disruption of the gut barrier during inflammation: Should we abandon traditional epithelial cell lines and switch to intestinal organoids? - Lechuga, Susana; Braga-Neto, Manuel B.; Naydenov, Nayden G.; Rieder, Florian; Ivanov, Andrei I. (Frontiers in Immunology, 2023)
Disruption of the intestinal epithelial barrier is a hallmark of mucosal inflammation. It increases exposure of the immune system to luminal microbes, triggering a perpetuating inflammatory response. For several decades, the inflammatory stimuli-induced breakdown of the human gut barrier was studied in vitro by using colon cancer derived epithelial cell lines. While providing a wealth of important data, these cell lines do not completely mimic the morphology and function of normal human intestinal epithelial cells (IEC) due to cancer-related chromosomal abnormalities and oncogenic mutations. The development of human intestinal organoids provided a physiologically-relevant experimental platform to study homeostatic regulation and disease-dependent dysfunctions of the intestinal epithelial barrier. There is need to align and integrate the emerging data obtained with intestinal organoids and classical studies that utilized colon cancer cell lines. This review discusses the utilization of human intestinal organoids to dissect the roles and mechanisms of gut barrier disruption during mucosal inflammation. We summarize available data generated with two major types of organoids derived from either intestinal crypts or induced pluripotent stem cells and compare them to the results of earlier studies with conventional cell lines. We identify research areas where the complementary use of colon cancer-derived cell lines and organoids advance our understanding of epithelial barrier dysfunctions in the inflamed gut and identify unique questions that could be addressed only by using the intestinal organoid platforms.